DETERMINANTS OF INTRA-INDUSTRY TRADE BETWEEN ECOWAS AND EUROPEAN UNION (2014)
Economic Community of West African States‘ (ECOWAS) total trade has reflected deficit in the last two decades. It was $1.42 billion in 1990, increased to $3.32 billion in 2000 and $6.24 billion in 2009. This trade imbalance in the ECOWAS region can be traced to the dominance of primary over manufactured products in the region‘s exports. However, the imbalance can be reversed with trade in similar products that is Intra-Industry Trade (IIT) between the region and her highest trade partner, (European Union (EU)). Empirical studies have examined IIT among developed countries (horizontal-IIT), while adequate attention has not been paid to it between developing and developed countries (vertical-IIT). This study, therefore, examined the extent and determinants of IIT in both final and intermediate products between ECOWAS and EU. The Augmented Gravity Model, based on Flam-Helpman‘s North-South trade framework, was estimated to determine the factors affecting vertical-IIT between ECOWAS and EU. The model considered income distribution in partner countries, factor endowment, product differentiation, Foreign Direct Investment (FDI), relative country size, weighted distance, capital-labour ratio, exchange rate and tariff as determinants of vertical-IIT. The Grubel-Lloyd index, bounded by 0 and 1, was used to compute the dependent variable (extent of vertical-IIT). A closer to one Grubel-Lloyd index implied higher level of IIT. Data were collected from the World Integrated Trade Solution and World Development Indicators from 2001 to 2011. Fractional Logit Regression technique that took note of the nature of the dependent variable was estimated while controlling for heteroscedasticity. The estimations were done for both final and intermediate products. Hausman-test and LM-test were used to confirm the robustness of the model and statistical significance at P≤0.05. Vertical-IIT in both final and intermediate products between ECOWAS and EU were low. Average vertical-IIT in final products between the two regions increased from 0.1 in 2001 to 0.3 in 2011, while that of vertical-IIT in intermediate products increased from 0.1 in 2001 to 0.2 in 2011. Income distribution, factor endowment, products differentiation and FDI improved vertical-IIT in final products. Specifically, if these factors were increased by UNIVERSITY OF IBADAN LIBRARY iii 1.0%, vertical-IIT in final products would improve by 10.0% 4.0%, 4.0% and 11.1%, respectively. However, the coefficients of the weighted distance (-0.02) and tariff (-0.006) were indicative of inverse change in vertical-IIT in final products by 2.0% and 0.06% in response to 1.0% change in the two factors respectively. For the vertical-IIT in intermediate products, 1.0% change in factor endowment, product differentiation, income distribution and relative country size improved vertical-IIT by 5.9%, 2.2%, 4.1%, and 3.7%, respectively. The coefficients of FDI (0.19) implied that vertical-IIT in intermediate products increased by 19.0% in response to 1.0% change in FDI. Product differentiation and foreign direct investment have positive and significant impact on intra-industry trade in final and intermediate products between Economic Community of West African States and European Union. It is important, therefore, to attract more multinational firms into the region. Efforts should also be made to improve on the level of products differentiation in the region. Keywords: Intra-industry trade, Fractional logit model, Intermediate products, products differentiation. Word count: 495